Seismic vulnerability assessment of low to mid-rise RC buildings addressing prevailing design and construction practices in the Northeastern region of the Indian subcontinent: A case study based approach. (October 2021) - Chandra Dutta, Sekhar; Halder, Lipika; Prasad Sharma, Richi
Abstract: RC buildings with infilled masonry are very common in Northeast India and neighbouring countries like Nepal, along with open ground storey (OGS) buildings and bare framed buildings. In this region, due to the low financial capacity of the owners, most of the private buildings are constructed either with a consultation to local masons without any engineering input or by the engineers, mainly based on the thumb-rules. In such cases, design and construction quality (DCQ) and non-uniform distribution of the infill wall increase the damage level. Herein, an effort has been made to quantify the influence of DCQ, infill wall distribution, and their combined effect on seismic response. The vulnerability of low to mid-rise RC buildings is studied through fragility analysis using a simplistic nonlinear static analysis based method. The fragility curves show that inferior design and construction quality and the absence of masonry infill on the ground floor increases susceptibility to the manifold. However, the vulnerability of these RC buildings, including the ones with an open ground storey, can be decreased through well design and construction practices under controlled supervision. Thus, it may avoid collapse mainly for low seismic hazards that are often striking the Northeastern region of the Indian subcontinent and many other countries relatively more frequently than the very severe event. The overall observations that came out from the study may prove beneficial for selecting the suitable building configuration by design engineers, keeping a balance between safety and economy. The results obtained in the form of various curves and tables may be used for the preliminary design of new buildings and seismic risk assessment of existing buildings of such regions as well as of other areas with similar building typologies. Hence, the study may prove useful not only in the design offices, but the approach outlined in the study may be applied to various regions for vulnerability assessment, using the methodology having a fair compromise between rigour and accuracy. Finally, a large set of results generated following such a process may pave the way for refining design guidelines for performance-based design.